(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Dysregulation of CD4+ T cell subsets participates in the pathogenesis of immunoglobulin A nephropathy (IgAN). Vitamin D has immunomodulatory functions. This study aims to investigate the regulatory effect of vitamin D3 on T helper- regulatory T (Th17-Treg) cells balance in rats with IgAN. Materials and Methods. Sprague-Dawley rats were randomly assigned to a normal group (n = 6), an IgAN model group (n = 5), a prednisone treatment IgAN group (n = 6), a 1,25-dihydroxyvitamin D3 IgAN group (n = 6), and prednisone plus 1,25-dihydroxyvitamin D3 treatment group (n = 6). At week 12, the 24-hour urine protein excretion and erythrocyte count and renal pathological changes were determined, and serum interleukin-17 and Treg cell levels were measured in blood. Results. The urine protein content and the number of erythrocytes were lower in the vitamin D group than in the model group (P < .01), but higher than in the prednisone groups (P <0.01). The pathological impairments in the glomerular mesangium, renal tubule, and renal interstitium decreased in response to treatment with prednisone with and without 1,25-dihydroxyvitamin D3. Serum interleukin-17 level in the vitamin D and prednisone plus vitamin D groups was lower than in the prednisone group (P < .05). The Treg cells in the vitamin D and prednisone plus vitamin D groups showed higher levels than in the prednisone group (P < .01). Conclusions. Vitamin D3 can regulate the Th17/Treg balance and reduce the level of protein and blood in the urine of rats with IgAN.